Empirical analysis of a self-service check-in implementation in Singapore Changi Airport - Lee, CKM (2014)
The purpose of this paper is to provide an empirical analysis an airport passenger operation and to improve its efficiency. An investigation was conducted to evaluate the quantitative and qualitative efficiency of the self-service check-in booth in Singapore Changi Airport. Through Arena simulation software, this investigation gives an estimation of how much processing time and queuing time the self-service check-in booths have been reduced, providing a quantitative analysis of the selfservice check-in booth. A modified technology acceptance model featuring a prediction of how well passengers accept this new concept has also been used in this investigation. The results show that the self-service checkin booth’s operation is generally efficient based on quantitative and qualitative analysis, providing a recommendable service to customers.